2005
DOI: 10.1111/j.1572-0241.2005.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial of Esomeprazole- versus Pantoprazole-Based Triple Therapy for Helicobacter pylori Eradication

Abstract: Esomeprazole-based triple therapy demonstrated a higher eradication rate than pantoprazole-based regimen. The differences in eradiation efficacies between the two study groups may be related to the more powerful acid inhibition effect and stronger anti-H. pylori activity of esomeprazole compared to pantoprazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 25 publications
2
46
0
1
Order By: Relevance
“…That report also suggested that neither esomeprazole dosage nor dosing duration have additive effects on H. pylori eradication rates. Although some reports have shown that esomeprazole at 20 mg has an H. pylori eradication rate similar to that of omeprazole at 20 mg,63,64 the rate has also been shown to significantly differ between esomeprazole-based and other PPI-based regimens, such as pantoprazole-based treatment (ITT analysis: 94% vs 82%; P = 0.009) 65…”
Section: H Pylori Eradication Therapy In Japanmentioning
confidence: 96%
“…That report also suggested that neither esomeprazole dosage nor dosing duration have additive effects on H. pylori eradication rates. Although some reports have shown that esomeprazole at 20 mg has an H. pylori eradication rate similar to that of omeprazole at 20 mg,63,64 the rate has also been shown to significantly differ between esomeprazole-based and other PPI-based regimens, such as pantoprazole-based treatment (ITT analysis: 94% vs 82%; P = 0.009) 65…”
Section: H Pylori Eradication Therapy In Japanmentioning
confidence: 96%
“…It is known that the CYP2C19 isoenzyme exhibits genetic polymorphism, where approximately 3% of Caucasians and 15–20% of Asians are poor metabolizers. Because esomeprazole metabolism is affected to a much smaller extent, there is less inter-patient variability between poor and extensive metabolizers of CYP2C19 [4]. Thus, the greater and more consistent bioavailability of esomeprazole provides a rationale for its superior control of gastric acid secretion and improved clinical efficacy compared with omeprazole.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of our meta-analysis showed that the efficacy of esomeprazole and omeprazole with respect to H. pylori eradication were not different when combined with two antibiotics. A recent study showed that the high dose of esomeprazole (40 mg twice daily) in triple therapy may improve H. pylori eradication relative to omeprazole-based therapy, but only for homologous extensive metabolizers of CYP2C19 [4]. …”
Section: Discussionmentioning
confidence: 99%
“…According to our previous study, the eradication rate of standard triple therapy is 82% (27). It is estimated that we required Ն102 patients in each treatment group to demonstrate a 10% absolute difference in the eradication rate with a type I error of 0.05 and a type II error and power of 80%, assuming a 5% loss to follow-up.…”
Section: Methodsmentioning
confidence: 99%